2021
DOI: 10.1007/s13399-020-01231-w
|View full text |Cite
|
Sign up to set email alerts
|

Developing a biorefinery from spent coffee grounds using subcritical water and hydrothermal carbonisation

Abstract: Spent coffee grounds (SCGs) have been extensively investigated as a feedstock to produce fuels, specialty chemicals and materials. Whilst a few reports have used cascade processes to generate several products from SCG, this work takes the novel approach of using integrated subcritical water extraction (SWE) and hydrothermal carbonisation (HTC) to derive three products: a bioactive extract, a protein isolate (SCG PI) and solid fuel. SWE and HTC processes were optimized producing an antioxidant rich extract, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The biochar of HHV of different biomasses is shown in Table 5. Previous HHV studies were compared with the HHV of this study to assess the potential for biochar through HTC, and SCGs were found to have a higher HHV than the other biomass samples, indicating their potential as a valuable fuel source through HTC conversion [32][33][34]. The producing biochar using SCGs has been carried out in a variety of ways, and as a result, the possibility of biochar is fully demonstrated not only in this research's results but also in previous research.…”
Section: Htc Of Scgs At Different Reaction Timesmentioning
confidence: 99%
“…The biochar of HHV of different biomasses is shown in Table 5. Previous HHV studies were compared with the HHV of this study to assess the potential for biochar through HTC, and SCGs were found to have a higher HHV than the other biomass samples, indicating their potential as a valuable fuel source through HTC conversion [32][33][34]. The producing biochar using SCGs has been carried out in a variety of ways, and as a result, the possibility of biochar is fully demonstrated not only in this research's results but also in previous research.…”
Section: Htc Of Scgs At Different Reaction Timesmentioning
confidence: 99%
“…where: ω(AA) i is the amino acid individual mass fraction (mg/ g); M r (AA) i is the amino acid molecular mass (g/mol); N AAi is the mass of N in the amino acid (mg/g); f n is the nitrogen-to-protein conversion factor, which for SCG is 7.79 [19].…”
Section: Characterisation Of Scg-phmentioning
confidence: 99%
“…with 1260 autosampler and variable wavelength detector (VWD). Run methods were as previously published [19].…”
Section: Characterisation Of Scg-phmentioning
confidence: 99%
See 2 more Smart Citations